Peat Ecosystem: Teachers' knowledge and perception, and its integration in learning biology - Bambang Hariyadi; Agus Subagyo; Winda Dwi Kartika (Universitas Ahmad Dahlan, 2021)
The improper uses of peatlands degrade the lands, making them vulnerable to fire. Restoration and conservation of Indonesian peatlands have not succeeded, yet the forest fires tend to increase in severity and frequency. Therefore, it is urgent to have more systematic efforts to conserve the peatlands through education, mainly in schools. This study aims to assess the knowledge and perceptions of high school biology teachers about the peatland ecosystem and identify the potential for integrating peatland-associated materials in learning biology. Data and information were collected through observation, online questionnaires, literature reviews, and focus group discussions. The data were analyzed qualitatively to reveal the biology teacher's knowledge and perceptions about peatlands. Although peatland is a vital resource on the east coast of Jambi Province, most biology teachers in the region do not have good knowledge about peatland. However, the teachers aware of the importance of integrating peatland material in learning biology. They argue that the integration facilitates students to understand the surrounding environment, including the peatland.Â Therefore, in the long run, they could actively involve in protecting and conserving the peatland. This research has identified several peatlands-associated materials that are relevant to be integrated into biology learning.